Measuring laminar burning velocities using constant volume combustion vessel techniques - Hinton, N (2014)
The laminar burning velocity is an important fundamental property of a fuel-air mixture at given conditions of temperature and pressure. Knowledge of burning velocities is required as an input for combustion models, including engine simulations, and the validation of chemical kinetic mechanisms. It is also important to understand the effect of stretch upon laminar flames, to correct for stretch and determine true (unstretched) laminar burning velocities, but also for modelling combustion where stretch rates are high, such as turbulent combustion models. A constant volume combustion vessel has been used in this work to determine burning velocities using two methods: a) flame speed measurements during the constant pressure period, and b) analysis of the pressure rise data. Consistency between these two techniques has been demonstrated for the first time. Flame front imaging and linear extrapolation of flame speed has been used to determine unstretched flame speeds at constant pressure and burned gas Markstein lengths. Measurement of the pressure rise during constant volume combustion has been used along with a numerical multi-zone combustion model to determine burning velocities for elevated temperatures and pressures as the unburned gas ahead of the spherically expanding flame front is compressed isentropically. This burning velocity data is correlated using a 14 term correlation to account for the effects of equivalence ratio, temperature, pressure and fraction of diluents. This correlation has been modified from an existing 12 term correlation to more accurately represent the dependence of burning velocity upon temperature and pressure. A number of fuels have been tested in the combustion vessel. Biogas (mixtures of CH4 and CO2) has been tested for a range of equivalence ratios (0.7–1.4), with initial temperatures of 298, 380 and 450 K, initial pressures of 1, 2 and 4 bar and CO2 fractions of up to 40% by mole. Hydrous ethanol has been tested at the same conditions (apart from 298 K due to the need to vaporise the ethanol), and for fractions of water up to 40% by volume. Binary, ternary and quaternary blends of toluene, n-heptane, ethanol and iso-octane (THEO) have been tested for stoichiometric mixtures only, at 380 and 450 K, and 1, 2 and 4 bar, to represent surrogate gasoline blended with ethanol. For all fuels, correlation coefficients have been obtained to represent the burning velocities over wide ranging conditions. Common trends are seen, such as the reduction in burning velocity with pressure and increase with temperature. In the case of biogas, increasing CO2 results in a decrease in burning velocity, a shift in peak burning velocity towards stoichiometric, a decrease in burned gas Markstein length and a delayed onset of cellularity. For hydrous ethanol the reduction in burning velocity as H2O content is increased is more noticeably non-linear, and whilst the onset of cellularity is delayed, the effect on Markstein length is minor. Chemical kinetic simulations are performed to replicate the conditions for biogas mixtures using the GRI 3.0 mechanism and the FlameMaster package. For hydrous ethanol, simulations were performed by Carsten Olm at Eötvös Loránd University, using the OpenSMOKE 1D premixed flame solver. In both cases, good agreement with experimental results is seen. Tests have also been performed using a single cylinder optical engine to compare the results of the hydrous ethanol tests with early burn combustion, and a good comparison is seen. Results from tests on THEO fuels are compared with mixing rules developed in the literature to enable burning velocities of blends to be determined from knowledge of that of the pure components alone. A variety of rules are compared, and it is found that in most cases, the best approximation is found by using the rule in which the burning velocity of the blend is represented by weighting by the energy fraction of the individual components.